Leaflet Media to Increase Knowledge and Attitudes of Pregnant Women in Exclusive Breastfeeding to Prevent Stunting - Ana Sundari; Budi Astyandini; Rozikhan Rozikhan (Indonesian Journal of Global Health Research, 2024)
Scaling Up Nutrition (SUN) Movement is one of the global efforts from various countries to strengthen commitments and action plans to accelerate nutrition improvement, especially nutrition management from 1,000 days from pregnancy to 2 years old. Breastfeeding for toddlers are related to the incidence of stunting. Efforts that can be made to increase knowledge by providing counseling on exclusive breastfeeding using interactive media (leaflets). Objective: This study aims to determine the effect leaflet on increasing the knowledge and attitudes of pregnant women in exclusive breastfeeding to prevent stunting. Method: This study used  one group pretest and posttest design, samples are pregnant women in the Bandengan Village with nonprobability sampling techniques, totaling 30 mothers. Data were collected using questionnaires, analyzed with Wilcoxon Test on knowledge variables and t-tests on attitude variables. Results: There is an effect of leaflets media on increasing the knowledge of pregnant women in exclusive breastfeeding (p-value of 0.000 < 0,05, the mean value is 9.70 to 15.33) and the increase in attitude ( p-value of 0.006 < 0,05, the mean value is 23.13 to 24.07).  Conclusions: Leaflet is proven to be able to improve the knowledge and attitudes of pregnant women in exclusive breastfeeding.